Effectiveness of bag bath on microbial load: clinical trial - Paulela, Debora Cristina [UNESP]; Mangini Bocchi, Silvia Cristina [UNESP]; Mondelli, Alessandro Lia [UNESP]; Martin, Luiz Cuadrado [UNESP]; Sobrinho, Adriana Regina [UNESP] (Univ Fed Sao Paulo, Dept Enfermagen, 2018)
Objective: To assess the effectiveness of bag bath on inpatient skin microbial load. Methods: This was a parallel, randomized clinical trial with an intervention group (bag bath) and a control group (conventional bed bath), conducted in a public hospital in Sao Paulo, Brazil, from November 2014 to December 2015. The participants were adult and older inpatients, bedridden and depending on the procedure. The product assessed was Bag Bath (R). Results: The microbial load decreased in the intervention group (20 patients), while it increased significantly (p < 0.001) in the control group (20 patients). The estimated efficacy of the product for bag bath was 90%, compared with 20% for the conventional bed bath. Conclusion: The product assessed was 4.5 times more effective to decrease the inpatient skin microbial load when compared with the conventional bed bath, suggesting the need for nursing teams to re-evaluate this procedure.
Keywords: Baths; Cross infection; Nursing care; Personal hygiene products; Evaluation of the efficacy-effectiveness of interventions